2006
DOI: 10.1890/0012-9658(2006)87[922:drisva]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Damage-Induced Resistance in Sagebrush: Volatiles Are Key to Intra- And Interplant Communication

Abstract: Airborne communication between individuals, called "eavesdropping" in this paper, can cause plants to become more resistant to herbivores when a neighbor has been experimentally clipped. The ecological relevance of this result has been in question, since individuals may be too far apart for this interaction to affect many plants in natural populations. We investigated induced resistance to herbivory in sagebrush, Artemisia tridentata, caused by experimental clipping of the focal plant and its neighbors. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
322
3
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(345 citation statements)
references
References 40 publications
(72 reference statements)
16
322
3
4
Order By: Relevance
“…Airborne signaling in the context of plant antiherbivore defense has been repeatedly reported and is likely to be a common phenomenon, since herbivoreinduced VOCs serve multiple functions, such as the attraction of predatory arthropods (Turlings et al, 1995;De Moraes et al, 1998;Thaler, 1999;Kessler and Baldwin, 2001), the repellence of herbivores (Birkett et al, 2000;De Moraes et al, 2001), and the within-plant signaling that leads to systemic responses to local damage (Karban et al, 2006;Frost et al, 2007;Heil and Silva Bueno, 2007). In this study, we report that airborne plant-plant signaling can also prime plant resistance against a pathogenic bacterium.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Airborne signaling in the context of plant antiherbivore defense has been repeatedly reported and is likely to be a common phenomenon, since herbivoreinduced VOCs serve multiple functions, such as the attraction of predatory arthropods (Turlings et al, 1995;De Moraes et al, 1998;Thaler, 1999;Kessler and Baldwin, 2001), the repellence of herbivores (Birkett et al, 2000;De Moraes et al, 2001), and the within-plant signaling that leads to systemic responses to local damage (Karban et al, 2006;Frost et al, 2007;Heil and Silva Bueno, 2007). In this study, we report that airborne plant-plant signaling can also prime plant resistance against a pathogenic bacterium.…”
Section: Discussionmentioning
confidence: 68%
“…In particular, green-leaf volatiles and other herbivore-induced volatile organic compounds (VOCs) can mediate the systemic response of plants to local herbivore damage (Karban et al, 2006;Frost et al, 2007;Heil and Silva Bueno, 2007). Since such VOCs move freely in the air, they may also affect neighboring plants and then mediate the phenomenon of "plant-plant communication," which has been found in taxonomically unrelated plants such as Arabidopsis (Arabidopsis thaliana), alder (Alnus glutinosa), corn (Zea mays), lima bean (Phaseolus lunatus), maple (Acer saccharum), sagebrush (Artemisia tridentata), and wild tobacco (Nicotiana attenuata; Baldwin and Schultz, 1983;Rhoades, 1983;Tscharntke et al, 2001;Engelberth et al, 2004;Heil and Kost, 2006;Karban et al, 2006;Paschold et al, 2006;Heil and Silva Bueno, 2007;Ton et al, 2007;Godard et al, 2008).…”
mentioning
confidence: 99%
“…Previous studies have suggested that plant behavior is simpler than that of animals. Now, however, plant biologists have discovered that experiential accumulation through conditioning can also significantly affect plant behavior [12,23,24]. Plants also have memory and communication behavior, even if they lack a central nervous system.…”
Section: Root System Coevolutionmentioning
confidence: 99%
“…In inter-plant signaling, cues that are emitted from damaged individual plant are received by neighboring individual plant and induce resistance in the receiver plant. Sagebrush (Artemisia tridentata) is known to use volatile cues to induce systemic resistance to herbivory within and between plants (socalled volatile communication) (Karban et al 2006). In the system of volatile communication of sagebrush, the area where the volatile communication occurred was within 60 cm from damaged individuals (Karban et al 2006) and the components of volatiles varied among individuals (Karban and Shiojiri 2009).…”
mentioning
confidence: 99%
“…Sagebrush (Artemisia tridentata) is known to use volatile cues to induce systemic resistance to herbivory within and between plants (socalled volatile communication) (Karban et al 2006). In the system of volatile communication of sagebrush, the area where the volatile communication occurred was within 60 cm from damaged individuals (Karban et al 2006) and the components of volatiles varied among individuals (Karban and Shiojiri 2009). Moreover, when sagebrush received volatiles from self branches or clonally potted genetically identical branches, it suffered less damage than when it received volatiles from genetically different potted branches (Karban and Shiojiri 2009).…”
mentioning
confidence: 99%